2015
DOI: 10.1111/pere.12104
|View full text |Cite
|
Sign up to set email alerts
|

Cherish the good times: Relational savoring in parents of infants and toddlers

Abstract: Savoring, or prolonging emotions associated with positive events, improves emotion and life satisfaction; little work, however, focuses on the savoring of interpersonal experiences, termed relational savoring. In a sample of 435 parents, the authors evaluated the impact of relational savoring on emotion and parent–child relationship satisfaction compared to a personal savoring and neutral control condition. Two years later, the authors reassessed parents' feelings of closeness with their children in a subsampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 46 publications
8
73
1
Order By: Relevance
“…Building on Bryant's () foundational work on savoring, the process of prolonging, intensifying, and appreciating the positive emotions attached to experiences, relational savoring involves the purposeful activation of and focused reflection on moments of positive connection between the self and another person (Borelli, Sbarra et al., ). Consistent with theorizing, our prior work has suggested that parental attachment avoidance, as measured by self‐report, is associated with poorer relational savoring quality (Bond & Borelli, ), although in an experimental study comparing relational savoring to a control condition, we (Burkhart et al., ) found that although self‐reported attachment avoidance was inversely related to traitlike savoring, highly avoidant parents exhibited the largest gains in emotion and relationship satisfaction. Yet, despite the fact that avoidant parents reaped the most from the relational savoring exercise, based on our prior work (Bond & Borelli, ), it seems likely that the memories avoidant parents generate contain less SBS content.…”
Section: Attachment Avoidance and Emotional Deactivationsupporting
confidence: 80%
See 2 more Smart Citations
“…Building on Bryant's () foundational work on savoring, the process of prolonging, intensifying, and appreciating the positive emotions attached to experiences, relational savoring involves the purposeful activation of and focused reflection on moments of positive connection between the self and another person (Borelli, Sbarra et al., ). Consistent with theorizing, our prior work has suggested that parental attachment avoidance, as measured by self‐report, is associated with poorer relational savoring quality (Bond & Borelli, ), although in an experimental study comparing relational savoring to a control condition, we (Burkhart et al., ) found that although self‐reported attachment avoidance was inversely related to traitlike savoring, highly avoidant parents exhibited the largest gains in emotion and relationship satisfaction. Yet, despite the fact that avoidant parents reaped the most from the relational savoring exercise, based on our prior work (Bond & Borelli, ), it seems likely that the memories avoidant parents generate contain less SBS content.…”
Section: Attachment Avoidance and Emotional Deactivationsupporting
confidence: 80%
“…For the purpose of this study, we conducted focus groups comprised of parents of young children with the goal of eliciting information regarding which types of parenting situations parents of young children find stressful (see Burkhart et al, ). Based on these focus groups, we developed a vignette describing a stressful situation that focus group members suggested would elicit strong feelings of distress and helplessness in the parent, which ought to make RF especially difficult (Slade, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of techniques could plausibly be used to improve initiation of positive interactions in dyads with children with ASD. Mindfulnessbased interventions (Cachia et al 2016), relational savoring interventions (Burkhart et al 2015), and mentalizationbased interventions (Slade 2005) may help promote positive dyadic engagement, improve parental perception of dyadic interactions, and increase parental sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in line with broaden and build (Fredrickson, ), upregulating PA can help people develop strengths and flourish. For example, youth who exhibit higher levels of PA are rated higher on social competence (Isley, O'Neil, & Parke, ), and parents’ relational savoring (i.e., thinking of a best memory with one's child) can promote relationship closeness and satisfaction (Burkhart, Borelli, Rasmussen, & Sbarra, ). Moreover, these processes are cyclic wherein PA enhances one's relationships, and one's positive relationships will enhance people's PA (Ramsey & Gentzler, ).…”
Section: Moving Forwardmentioning
confidence: 99%